PENGARUH EMPOWERMENT DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI KELURAHAN GISIKGRONO, KOTA SEMARANG - Nurhidayah, Evinta Amalia; Ade, Sinar Hubtriyan; Nindhita, Yoga (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2024)
This research aims to analyze the influence of empowerment and the work environment on employee performance. The population in this study were 40 employees of Gisikdrono subdistrict, Semarang City. The sampling technique in this research used census sampling, namely using all sub-district employees in Gisikdrono District, Semarang City, totaling 40 people as the research sample. The analytical tools in this research include instrument tests (validity test, reliability test), classical assumption tests (normality test, multicollinearity test, heteroscedasticity test), multiple linear regression, hypothesis testing via t test, f test, and coefficient of determination test. The results of this research prove that empowerment has a coefficient on employee performance regression in a positive direction and a significance value of 0.049 < 0.05, meaning that empowerment has a positive and significant effect on employee performance and the work environment on employee performance obtained a regression coefficient in a positive direction and a significance value of 0.017 < 0.05, meaning that the work environment has a positive and significant effect on employee performance. The adj r2 value obtained was 0.583, which means that 58.3% of the variation in employee performance can be explained by independent variables such as empowerment and work environment. The conclusion of this research is that the empowerment and work environment variables have a positive and significant effect on employee performance. The suggestion of this research is that it is hoped that leaders in the Gisikdrono sub-district, Semarang, can optimize employee competency development training and implement knowledge sharing programs well so that competency and The work experience of seniors can be conveyed well by juniors so that employees have a strong determination to complete the work.